Meningkatkan Kemampuan Berpikir Kritis Peserta Didik dalam Pembelajaran IPA Melalui Penggunaan Modul Praktikum Berbasis KBTL - Pelupessy, Frelin; Latupeirissa, Asry Nelannya; Pulu, Sri Rahmadhani (Pattimura University, 2024)
Critical thinking skills are high-level thinking skills that every learner must have to understand and solve problems. However, what often happens is that most teachers do not sharpen children in developing critical thinking skills. This study aims to improve students’ critical thinking skills through the use of practicum modules based on Advanced Questioning Skills (KBTL) in science learning. The population in this study were all grade VIII students at Santoso Andreas Junior High School, as many as 12 students who were then referred to as research samples. This research is included in the type of quasi-experiment research by applying the One-Group Pre-Test Post-test research design. The instruments used are test questions and Learner Worksheets (LKPD). The data obtained were then analyzed descriptively and quantitatively, which aims to provide a true picture of the use of the KBTL practicum module on the critical thinking skills of students. Based on the analysis conducted, it can be seen that there is a significant change or increase in the critical thinking skills of students based on the average achievement score, both obtained in the Pre-test and Post-test with a percentage of 55.4%. These results can be further reviewed on the results obtained by students during the learning process through the LKPD work on the KBTL-based practicum module, with an average achievement score of 87.08. The N-Gain test was carried out with the calculation results showing a value of 0.87 and included in the high category. This indicates that the use of KBTL-based practicum modules has a significant impact on improving students’ critical thinking skills.